Kalam khabar dalam ayat-ayat al-Qur’an surah az-zukhruf: Studi Balaghah - Ananda, Rayhan Hafizh; Muassomah, Muassomah (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
Surah az-zukhruf contains verses of the Qur'an that contain information and affirmations of Allah to mankind. The themes raised are about the exaltation of Allah, the debate between Muslims and disbelievers and several other themes aimed at providing understanding and affirmation so that the effectiveness of information can be conveyed from people who do not know to people who deny. This research aims to determine the form of kalam khabar and its purpose contained in the utterances uttered by speakers (mutakallim) in the Qur'an, especially surah az-zukhruf along with its social, cultural and historical context. This research uses descriptive qualitative method, which is a literature study that examines the verses of the Qur'an with the approach of balaghah study. The source of data in this research is surah az-zukhruf which amounts to 89 verses of the Makkiyah surah. Then, the data of this study were collected through 2 stages, namely reading and recording. The analysis technique used in this research is interpreting and drawing conclusions in accordance with the research objectives. The results of this study show that the form of kalam khabar that tends to appear is kalam khabar ibtida'i with a percentage of 22 data (47%), while for kalam khabar thalabi has a percentage of 16 data (33%), the last is kalam khabar inkari whose percentage is 10 data (20%). So, it can be concluded that in surah az-zukhruf it tends to be used without taukid and also does not use a lot of taukid in its verses. The researcher concludes that there is a lot of information revealed by Allah to mankind through the verses in surah az-zukhruf.